GOLD-BEARING ARSENOPYRITE AND ITS FORMATION CONDITION AT THE OLYMPIADA AND VEDUGA GOLD DEPOSITS (YENISEI RANGE, SIBERIA) - Genkin A.D.; Wagner F.E.; Krylova T.L.; Tsepin A.I. (My University, 2002)
Possible reasons of a difference in modes of invisible gold occurrences in arsenopyrite at the Olympiada and Veduga deposits that are closely spatially situated and occur in a similar geological setting were considered. The arsenopyrite composition in both deposits was determined. It is nonstoichiometric and characterized by a prevalence of sulfur over arsenic. The Au content in arsenopyrite from Olympiada and Veduga is up to 2100 ppm and 1100 ppm, respectively. A Moessbauer study has shown the presence of metallic gold in arsenopyrite from Olympiada and chemically bound gold in the minerals from Veduga. New data on the unique Olympiada deposit, where arsenopyrite-bearing invisible metallic gold occurs, are given. A study of fluid inclusions in minerals syngenetic or crystallized coevally with arsenopyrite revealed the formation conditions of disseminated arsenopyrite bearing invisible gold. In the Olympiada deposit, arsenopyrite bearing invisible gold crystallized at temperatures above 400°C and pressures of 1.3 to 2.7 kbar in a heterogeneous environment. A predominant gaseous fluid consisted of nitrogen, methane, and minor CO2. A supersaturated aqueous-salt solution was recorded in rare three-phase fluid inclusions. In the Veduga deposit, arsenopyrite bearing chemically bound gold formed at lower temperatures of 300 to 420°C from low-saline solutions in the H2O-rich system with a prevalence of CO2. It is suggested that major factors defining the state of invisible gold in arsenopyrite were temperature and oxidation-reduction conditions of the mineral formation.